NiTiHf-based shape memory alloys. (November 2014) - Karaca, H. E.; Acar, E.; Tobe, H.; Saghaian, S. M.
Abstract : NiTiHf-based shape memory alloys have been receiving considerable attention for high temperature, high strength and two-way shape memory applications since they could have transformation temperatures above 100°C, shape memory effect under high stress (above 500 MPa) and superelasticity above 100°C. Moreover, their shape memory properties can be tailored by microstructural engineering. However, NiTiHf-based alloys have some drawbacks such as low ductility and high slope in stress induced martensite transformation region. In order to overcome these limitations, studies have been focused on microstructural engineering by aging, alloying and processing. It has been revealed that microstructural control is crucial to govern the shape memory properties (e.g. transformation temperatures, matrix strength, shape recovery strain, twinning type, etc.) of NiTiHf-based alloys. A summary of the most recent improvements on selected NiTiHf-based systems is presented to point out their significant shape memory properties, effects of alloying, aging and microstructure of transforming phases and precipitates.